The development and validation of the clinicians' attitudes towards the impact of cognitive errors (CATChES) in clinical decision making questionnaire tool - Ab Aziz, Adlihafizi (2016)
Abstract Introduction Despite their impact on diagnostic accuracy, there is a paucity of literature on questionnaire tool to assess the clinicians‟ attitudes toward cognitive errors. A validation was study conducted to develop a questionnaire tool to evaluate the Clinician‟s Attitude Towards the impact of Cognitive Errors (CATChES) in clinical decision making. Methods This questionnaire is divided into two parts; Part A is to evaluate the clinicians‟ attitude towards cognitive errors in clinical decision making while Part B is to evaluate their attitude towards specific cognitive errors. For Part A, construct validation using exploratory factor analysis (EFA) was performed. For Part B, content validation using item level content validity index (i-CVI) and modified kappa (*) was performed. Results For EFA of Part A shows a two-factor model with total variance extraction of 60%. Two items were deleted. The EFA was then repeated with all factor loadings above the cut-off value of >0.5. The Cronbach‟s alphas for both factors were above 0.6. For Part B, the content validity is acceptable with values of i-CVI of 0.89 and above in terms of their relevance. Modified kappa was shown to be 0.89 and above for all items and rated as “excellent”. Conclusion The CATChES questionnaire tool is a valid questionnaire tool to evaluate the attitude among clinicians toward cognitive errors in clinical decision making.